(untitled) (Journal of Engineering, 2010)
In the present work, the step by step technique is used to predict the performance of the power plant condenser. The procedure includes the calculation of pressure distribution, condensation temperature, water inlet and outlet temperature, condensation load distribution and single phase heat transfer sub-cooling. A quasi two dimensions model is applied, one in the tube water direction and the other in the vapor direction. It is applied with different operating conditions of the condenser such as operating pressure, air percentage mixed with steam, cooling water temperature and fouling factor on tube side for summer and winter seasons. The present model revealed that the fouling resistance has a great effect and plays the major part of the decline in the condenser performance. This is because it decreases the overall heat transfer coefficient and condensation rate. The performance of the condenser when the cooling water enters at the lower pass is better than the upper pass, due to the balance in the distribution of the heat transfer and the condensation rate between tube passes. The model is verified with field operating conditions of Southern Baghdad thermal power station. It has revealed that there is a good agreement between the field data and the present technique. The accuracy fell within (98) % and (89) % for the cooling water temperature prediction for summer and winter respectively, while it showed accuracy of (98) % and (99) % for the condensate exit temperature prediction for summer and winter respectively.